The influence of recovery treatment on the immune status of children with recurrent respiratory infections - O.I. Lemko; S.V. Lukashchuk; N.V. Vantyukh; M.I. Popadinets (Zaslavsky O.Yu., 2017)
Background. Recurrent respiratory diseases are the most common pathology of childhood, they may be accompanied by suppression of the immune system and form the basis for the development of chronic inflammatory processes in the bronchopulmonary system at older age. Materials and methods. 58 sickly children and 61 patients aged 6-11 years with recurrent bronchitis were observed, the children were beyond the acute period. The phagocytic activity of neutrophils and monocytes and their phagocytic number, as well as the number of CD3+-, CD4+-, CD8+-cells with the ratio of CD4+- to CD8+-lymphocytes were determined. Treatment was carried according to three sets. The first one included 18 sessions of haloaerosol therapy. The second one provided a shortened course of haloaerosol therapy with the prescription of singlet-oxygen therapy, the third was conducted similarly to the second one with the additional prescription of vibroacoustic influence on the chest. Results. It was found that disturbances of nonspecific defense persist in the examined children beyond the acute period, which are manifested by a significant decrease in the absorption properties of neutrophils and monocytes. There were also changes in cellular immunity with manifestation of imbalance in the main subpopulations of T-lymphocytes and a significant decrease in the CD4+-/CD8+-lymphocytes ratio, more pronounced in patients with recurrent bronchitis. These changes indicate the need for immunorehabilitation treatment. Haloaerosol therapy in both groups of children leads to a significant improvement or normalization of the absorption properties of neutrophils and monocytes, and also helps to eliminate T-cell imbalance and to direct T-cell differentiation into the normal course. In sickly children, the increase in immunorehabilitation effects is possible with the use of one or two additional curative factors, which enables to reduce the course of haloaerosol therapy to 13 sessions. In patients with recurrent bronchitis, the most significant immunorehabilitation effect was achieved only by using two therapeutic factors on the background of the reduced regimen of haloaerosol therapy. Conclusions. The use of haloaerosol therapy in the recovery treatment of children with frequent and recurrent respiratory diseases provides a pronounced immunocorrective effect.